Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1074/jbc.m003132200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent Regulation of the Motor Activity of Myosin V

Abstract: Mouse myosin V constructs were produced that consisted of the myosin motor domain plus either one IQ motif (M5IQ1), two IQ motifs (M5IQ2), a complete set of six IQ motifs (SHM5), or the complete IQ motifs plus the coiled-coil domain (thus permitting formation of a double-headed structure, DHM5) and expressed in Sf9 cells. The actin-activated ATPase activity of all constructs except M5IQ1 was inhibited above pCa 5, but this inhibition was completely reversed by addition of exogenous calmodulin. At the same Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
92
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 34 publications
(46 reference statements)
14
92
0
Order By: Relevance
“…The slower cycling rate is also consistent with the actin gliding velocity; myosin Vb exhibited approximately twothirds of the velocity of myosin Va (43,58).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The slower cycling rate is also consistent with the actin gliding velocity; myosin Vb exhibited approximately twothirds of the velocity of myosin Va (43,58).…”
Section: Discussionsupporting
confidence: 71%
“…However, there are the regions in the motor domain of myosin Vb whose sequences are quite different from that of myosin Va. Among them, of interest is the loop 2 region that has been suggested to influence the actin binding property of myosin (43)(44)(45)(46)(47) since the K actin of myosin Vb is significantly higher than that of myosin Va. Figure 12 shows the amino acid sequence comparison between human myosin Va and myosin Vb in the motor domain. The loop 2 sequence of myosin Vb is unique and quite different from that of myosin Va.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in a bacterial two-hybrid assay, which is a modification of the yeast two-hybrid method, indicated that the six IQ-motifs of the neck bind to syntaxin-1A as well as CaM, although the first IQ alone does not mediate binding ( Figure 5E). Collectively, these results demonstrate that the binding site for syntaxin-1A is in the neck of myosin-Va.CaM is known to be released from the neck of myosin-Va in the presence of micromolar Ca 2ϩ (Cameron et al, 1998;Homma et al, 2000). We confirmed that preincubation of myosin-Va with Ca 2ϩ released the bound CaM ( Figure 5F).…”
supporting
confidence: 74%
“…Recombinant myosin-V (DHM5; ) was produced in Sf9 cells as described previously (Homma et al, 2000) or by in vitro translation (Promega, Madison, WI) using the mouse dilute cDNA (gift of N. A. Jenkins, University of Sao Paolo, Ribeirao Preto, Brazil; Mercer et al, 1991). DHM5 was detected with anti-myosin-Va head antibody (gift of R. E. Larson, National Cancer Institute, Frederick, MD; Nascimento et al, 1996;Evans et al, 1998).…”
Section: Biochemical and Molecular Biological Techniques For Assessinmentioning
confidence: 99%
“…MLC 20 was phosphorylated by MLCK and PKC as described (Ikebe and Hartshorne, 1985a;Ikebe et al, 1987). To analyze the fraction of the expressed MLC 20 incorporated into myosin II, we have used an ATP-dependent actin-binding activity of myosin II as described previously (Homma et al, 2000;Wei and Adelstein, 2000) with slight modifications. MEF/3T3 cells expressing myc-tagged MLC 20 s were lysed in buffer I (50 mM Tris-HCl, pH 7.5, 200 mM NaCl, 5 mM MgCl 2 , 2 mM EGTA, 1 mM dithiothreitol, 0.2 mM N-␣-p-tosyl-l-lysine chloromethl ketone [TLCK], 0.2 mM tosyl-phenylalanyl chloromethyl ketone [TPCK], 10 g/ml leupeptin, 2 mM phenylmethylsulfonyl fluoride, and 0.01% IGEPAL CA-630) with 2 mM ATP by sonication.…”
mentioning
confidence: 99%